Meteorology and dust in the central Sahara: Observations from Fennec supersite‐1 during the June 2011 Intensive Observation Period. Issue 10 (23rd May 2013) - Marsham, J. H.; Hobby, M.; Allen, C. J. T.; Banks, J. R.; Bart, M.; Brooks, B. J.; Cavazos‐Guerra, C.; Engelstaedter, S.; Gascoyne, M.; Lima, A. R.; Martins, J. V.; McQuaid, J. B.; et al.
Abstract: [1] We describe observations from the Fennec supersite at Bordj Badji Mokhtar (BBM) made during the June 2011 Fennec Intensive Observation Period. These are the first detailed in situ observations of meteorology and dust from the central Sahara, close to the center of the Saharan heat low and the summertime dust maximum. Historically, a shortage of such Saharan observations has created problems for evaluating processes, models, and remote sensing. There was a monsoon influence at BBM before 8 June and after 12 June, with dry Harmattan winds in between. A split boundary layer, generated by ventilation from the Atlantic, persisted during the drier phase. Extensive cold pools (haboobs) and microburst‐type events were regularly observed. Moisture reached BBM at night from the monsoon and the embedded haboobs. As well as the regularly occurring nocturnal low‐level jet (LLJ), a Saharan upper boundary layer (650 hPa) jet was observed, where winds feel drag from dry convection in the afternoon. This jet is linked to the diurnal cycles of moisture and cloud. Most dust was observed in the cloudier monsoon‐affected periods, and covarying dust and cloud amounts explain most of the variations in shortwave radiation that control the surface sensible flux. Dustiness is related to a standard parameterization of uplift using 10 m winds ("uplift potential"), and this is used to estimate uplift. Around 50% of uplift is nocturnal. Around 30% is from the LLJ, and 50% is from haboobs, which are mainly nocturnal. This demonstrates, for the first time from observations, the key role of haboobs, which are problematic for models. Key Points: First detailed observations from the central Sahara (upper BL jet observed) Most dust in moist air. Together, dust & cloud control surface energy balance ~50% of dust uplift is nocturnal. ~30% from the LLJ and ~50% from haboobs